(untitled) (Eurasian Medical Research Periodical, 2023)
The Aral-Sea shrinking to less than half of what it once was. Because of this, more than 40,000 square kilometers of the highly salinized seabed are now exposed and frequently buffeted by winds. This research compared children those are living in "the significantly impacted disaster area" (around 100-200 kilometers of the Aral-Sea) to children those are living in "the mildly affected disaster area" to look at respiratory tract symptoms and function (i.e., located almost 500 kilometers from the Aral-Sea). 250 kids aged 6 to 15 who resided in the research region and 100 students who lived in the reference area participated in a questionnaire-based interview. Both 250 children in the research region and 100 children in the reference area had pulmonary function testing. More study group individuals had a cough or were now wheezing, The % predicted forcedexpiratory-volume in 1 second (FEV-1) and dust exposure showed some indication of an inverse association during the summer, but the converse was true during the winter.Peak flowmetry indications between 100 and 80% of the appropriate value were regarded as a deviation from the norm for determining the severity of obstructive syndrome; There are three levels of the obstructive syndrome: mild (80–70%), mode speed (70–60%), and severe (less than 60%)